Atmospheric Composition and Cloud Cover Observations - Voiculescu, Mirela; Voiculescu, Mirela (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This is a Special Issue of Atmosphere presenting recent results of experimental and theoretical investigations of atmospheric compositions and clouds, largely based on remote sensing.
English
Keywords: Technology: general issues; atmospheric gases; sources; European regulations; aerosol typing; lidar; photometry; EARLINET; AERONET; WRF; PBL; simulation; meteorology; wildfire; CO2 emission; OCO-2; MISR; MINX; freezing rain; high-impact meteorological event; Carpathian lee cyclogenesis; climatology; cloud occurrence frequency; automatic camera image analysis; Saharan dust; aerosol remote sensing; sun-photometer; MODIS; n/a